Exploring the Anticancer Potential of Traditional Thai Medicinal Plants: A Focus on Dracaena loureiri and Its Effects on Non-Small-Cell Lung Cancer - Xiaomin Huang; Punnida Arjsri; Kamonwan Srisawad; Supachai Yodkeeree; Pornngarm Limtrakul (2024)
Non-small-cell lung cancer (NSCLC) is renowned for its aggressive and highly metastatic nature. In recent years, there has been a surge in interest regarding the therapeutic potential of traditional medicinal plants. Dracaena loureirin (D. loureirin), Ficus racemosa Linn. (F. racemosa), and Harrisonia perforata (Blanco) Merr. (H. perforata) are prominent traditional medicinal herbs in Thailand, recognized for their diverse biological activities, including antipyretic and anti-inflammatory effects. However, their prospective anti-cancer properties against NSCLC remain largely unexplored. This study aimed to evaluate the anti-cancer attributes of ethanolic extracts obtained from D. loureiri (DLEE), F. racemosa (FREE), and H. perforata (HPEE) against the A549 lung adenocarcinoma cell lines. Sulforhodamine B (SRB) assay results revealed that only DLEE exhibited cytotoxic effects on A549 cells, whereas FREE and HPEE showed no such cytotoxicity. To elucidate the anti-cancer mechanisms of DLEE, cell cycle and apoptosis assays were performed. The findings demonstrated that DLEE inhibited cell proliferation and induced cell cycle arrest at the G0/G1 phase in A549 cells through the downregulation of key cell cycle regulator proteins, including cyclin D1, CDK-2, and CDK-4. Furthermore, DLEE treatment facilitated apoptosis in A549 cells by suppressing anti-apoptotic proteins (Bcl-2, Bcl-xl, and survivin) and enhancing apoptotic proteins (cleaved-caspase-3 and cleaved-PARP-1). In summary, our study provides novel insights into the significant anti-cancer properties of DLEE against A549 cells. This work represents the first report suggesting that DLEE has the capability to impede the growth of A549 lung adenocarcinoma cells through the induction of apoptosis.